A Quasi-Hilbert Space and Its Properties - Jawad Al-Delfi (Al-Qadisiyah Journal of Pure Science, 2021)
This  paper  studies concept  of a  quasi-inner product space  and its  completeness  to get and prove some properties of quasi-Hilbert spaces. The best examples of  this notion are spaces  where  0<p<∞.